2022
DOI: 10.1002/macp.202200036
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Structure–Property Relationships of Charged Block Polymers

Abstract: Advancements in electronics and energy storage and conversion technologies brings with it myriads of exciting material design challenges. Charge-containing block polymers (BPs) offer unique features which can overcome some of these challenges and have thus aroused substantial interest within the field of designer soft materials. The properties of BPs are intricately coupled to the dynamic and rich nature of the nanostructured assemblies, which result from the phase separation between blocks. The introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 169 publications
(348 reference statements)
0
7
0
Order By: Relevance
“…The behavior observed for these samples can be explained in terms of the competition between two parallel mechanisms: (1) enhancing effect of nanoparticles on microphase separation and (2) formation of 3D network by nanoparticles. It is well‐known that the driving force for phase‐separated domain formation, which is the thermodynamic incompatibility between the two blocks, is strong in the absence of a convective field and while cooling 31,32 . It also should be noted that the high viscosity and domain network in the S30 matrix causes further constraints for nanoparticles to move toward each other, significantly hindering particle‐particle interactions that are the driving force to form a percolated nanoparticle structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior observed for these samples can be explained in terms of the competition between two parallel mechanisms: (1) enhancing effect of nanoparticles on microphase separation and (2) formation of 3D network by nanoparticles. It is well‐known that the driving force for phase‐separated domain formation, which is the thermodynamic incompatibility between the two blocks, is strong in the absence of a convective field and while cooling 31,32 . It also should be noted that the high viscosity and domain network in the S30 matrix causes further constraints for nanoparticles to move toward each other, significantly hindering particle‐particle interactions that are the driving force to form a percolated nanoparticle structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the driving force for phase-separated domain formation, which is the thermodynamic incompatibility between the two blocks, is strong in the absence of a convective field and while cooling. 31,32 It also should be noted that the high viscosity and domain network in the S30 matrix causes further constraints for nanoparticles to move toward each other, significantly hindering particle-particle interactions that are the driving force to form a percolated nanoparticle structure. In other words, favorable interaction between PS block and nanoparticles can reinforce the phaseseparated domain network by enhancing microphase separation at the expense of weakening the nanoparticles' 3D network.…”
Section: Melt State Rheological Behaviormentioning
confidence: 99%
“…In addition to conformational asymmetry, electrostatic interactions are capable of radically altering the shape and location of transition boundaries within the BP phase diagram. 19,22,23,33,42,90,91 This factor may be influencing the continued scarcity of ion-containing BPs which display complex spherical packing. 88,89,92−94 In one instance, Xie et al observed a C15 Laves phase over a narrow compositional window in a ternary blend of polystyrene (PS), poly(ethylene oxide) (PEO), and PS-b-PEO doped with lithium salts ([Li + ]/ [EO] = 0.06).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our understanding of block polymer (BP) thermodynamics has progressed substantially alongside advancements in the underlying theoretical models. Relative to the simplified instance of linear diblock copolymer self-assembly, , several thermodynamic driving forces have the ability to shift, deflect, flip, and unveil transition boundaries in unique fashions. The list of modifying parameters is extensive, and each addition couples a new dimension to the phase space. While there is still much to learn about BP self-assembly, this cornucopia of factors provides a vast and broadening landscape of exciting opportunities for soft material design. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation